ÐšÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ðµ â€“ Ñ„Ð°ÐºÑ‚Ð¾Ñ€ Ð¾Ð¿Ñ‚Ð¸Ð¼Ð¸Ð·Ð°Ñ†Ð¸Ð¸ Ñ‚ÐµÑ€Ð°Ð¿ÐµÐ²Ñ‚Ð¸Ñ‡ÐµÑÐºÐ¾Ð³Ð¾ ÑÑ„Ñ„ÐµÐºÑ‚Ð° Ð¿Ñ€Ð¾Ð´ÑƒÐºÑ‚Ð¾Ð² ÑÐ¼Ð±Ñ€Ð¸Ð¾Ñ„ÐµÑ‚Ð¾Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ð°Ñ€Ð½Ð¾Ð³Ð¾ ÐºÐ¾Ð¼Ð¿Ð»ÐµÐºÑÐ° (ÐŸÐÐ¤ÐŸÐš). Ð§Ð°ÑÑ‚ÑŒ II. ÐšÐ¾Ñ€Ñ€ÐµÐºÑ†Ð¸Ñ ÑÐ¾ÑÑ‚Ð¾ÑÐ½Ð¸Ñ Ð»Ð¸Ð¼Ñ„Ð¾Ð³ÐµÐ¼Ð¾Ð¿Ð¾ÑÑ‚Ð¸Ñ‡ÐµÑÐºÐ¾Ð³Ð¾ ÐºÐ¾Ð¼Ð¿Ð»ÐµÐºÑÐ° ÑÐºÑÐ¿ÐµÑ€Ð¸Ð¼ÐµÐ½Ñ‚Ð°Ð»ÑŒÐ½Ñ‹Ñ… Ð¶Ð¸Ð²Ð¾Ñ‚Ð½Ñ‹Ñ… Ñ ÐÐ˜Ð“Ð ÐºÐ»ÐµÑ‚ÐºÐ°Ð¼Ð¸ Ñ„ÐµÑ‚Ð°Ð»ÑŒÐ½Ð¾Ð¹ Ð¿ÐµÑ‡ÐµÐ½Ð¸ - Goltsev, A. N.; Popova, K. N.; Sirous, M. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
Therapeutic efficiency of fetal liver cells (FLCs) of different gestation terms when treating autoimmune hemolytic anemia (AIHA) has been evaluated. The fact of manifested correcting effect of FLCs in respect of different compartments of lymphohemopoietic complex (LHPC) in AIHA animals has been established. Manifestation extent of FLCs activity was shown to be determined by gestation term and material type. When summarising therapeutic effect according to all evaluated systems there was demonstrated that FLCs of certain gestation terms gained higher level of integral therapeutic potential following cryopreservation.